Petrogenesis of basaltic shergottite Northwest Africa 8657: Implications for fO2 correlations and element redistribution during shock melting in shergottites. (16th November 2017) - Howarth, Geoffrey H.; Udry, Arya; Day, James M. D.
Abstract: Northwest Africa (NWA) 8657 is an incompatible trace element‐enriched, low‐Al basaltic shergottite, similar in texture and chemistry to Shergotty, Zagami, and NWA 5298. It is composed of zoned pyroxene, maskelynite, merrillite, and Ti‐oxide minerals with minor apatite, silica, and pyrrhotite. Pyroxene grains are characterized by patchy zoning, with pigeonite or augite cores zoned to Fe‐rich pigeonite mantles. The cores have rounded morphologies and irregular margins. Combined with the low Ti/Al of the cores, the morphology and chemistry of the pyroxene grains are consistent with initial crystallization at depth (30–70 km) followed by partial resorption en route to the surface. Enriched rare earth element (REE) equilibrium melt compositions and calculated oxygen fugacities ( f O2 ) conditions for pigeonite cores indicate that the original parent melts were enriched shergottite magmas that staged in chambers at depth within the Martian crust. NWA 8657 does not represent a liquid but rather entrained a proportion of pyroxene crystals from magma chambers where fractional crystallization was occurring at depth. Variation between f O2 and bulk‐rock (La/Yb)N of the enriched and intermediate shergottites suggests that oxidation conditions and degree of incompatible element enrichment in the source may not be correlated, as thought previously. Shock melt pockets are characterized by an absence of phosphates and oxide minerals. It is likely that these phases were melted during shock. REEs were redistributed during this process into maskelynite and to a lesser extent the shock melt; however, the overall normalized REE profile of the shock melt is like that of the bulk‐rock, but at lower absolute concentrations. Overall, shock melting has had a significant effect on the mineralogy of NWA 8657, especially the distribution of phosphates, which may be significant for geochronological applications of this meteorite and other Martian meteorites with extensive shock melt.